2010
DOI: 10.1097/psy.0b013e3181dbbb7d
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms and Mortality in Patients After Kidney Transplantation: A Prospective Prevalent Cohort Study

Abstract: Depressive symptoms are an independent predictor of mortality in kidney transplanted patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
82
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(98 citation statements)
references
References 65 publications
9
82
1
2
Order By: Relevance
“…5,6 Among kidney transplant (kTx) recipients, depression is associated with reduced adherence and also with increased morbidity, graft loss, and mortality. [7][8][9][10][11][12][13] Poor sleep and various sleep problems are also frequent complaints among kTx recipients.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Among kidney transplant (kTx) recipients, depression is associated with reduced adherence and also with increased morbidity, graft loss, and mortality. [7][8][9][10][11][12][13] Poor sleep and various sleep problems are also frequent complaints among kTx recipients.…”
Section: Introductionmentioning
confidence: 99%
“…Among kidney transplant patients, depression also appears to play an important role in terms of kidney graft survival and patient mortality. [29][30][31][32] Dobbels et al found that depression was associated with a twofold increase in risk of graft failure, return to dialysis, and death with a functioning graft. 32 Novak et al found that depressed patients were at greater risk of death over the study follow-up compared to nondepressed clients.…”
mentioning
confidence: 99%
“…32 Novak et al found that depressed patients were at greater risk of death over the study follow-up compared to nondepressed clients. 29 The association between negative mood states and poor clinical outcomes in kidney transplant patients might be explained by several factors, for example, with nonadherence to treatment regimens. [33][34][35] Furthermore, depression in kidney transplant patients is associated with unhealthy behaviors including sedentary lifestyles, lower activity levels, and higher alcohol use, which may be associated with transplant-related outcomes.…”
mentioning
confidence: 99%
“…A prospective cohort study of 840 transplanted patients over 5-year period found a higher mortality rate in patients with depression as compared to patients without (21% vs 13%; p = 0.004). 47 Psychiatric symptoms could also affect the likelihood of patients who are put on the kidney transplant waiting list. Bayat et al found that the presence of a psychiatric disorder was a strong, independent factor in determining access to the transplant waitlist.…”
mentioning
confidence: 99%